A Comparative Study and Analysis of Deregulation of Indian Power Sector - Dr. Niteen G. Savagave, Suraj Deelip Pawar (International Journal of Advanced Science and Technology, 2020)
This paper is a conversation on rebuilding and bringing deregulation into the Indian Power System. In the modern era, the effect of deregulation on the power sector is significant. Although ownership per se does not seem to matter as much as increased competition, foreign banks appear to have acted as technological innovators during the deregulation process, thereby increasing the competitive pressure in the Indian Power Sector even further. Finally, along with the whole process of deregulation, our results also indicate an increase in risk-taking behaviour.